2009
DOI: 10.1073/pnas.0906390106
|View full text |Cite
|
Sign up to set email alerts
|

Structural imperatives impose diverse evolutionary constraints on helical membrane proteins

Abstract: The amino acid sequences of transmembrane regions of helical membrane proteins are highly constrained, diverging at slower rates than their extramembrane regions and than water-soluble proteins. Moreover, helical membrane proteins seem to fall into fewer families than water-soluble proteins. The reason for the differential restrictions on sequence remains unexplained. Here, we show that the evolution of transmembrane regions is slowed by a previously unrecognized structural constraint: Transmembrane regions bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 37 publications
2
78
3
Order By: Relevance
“…This algorithm is based on large-scale evaluation of proteins with established TMDs (Bernsel et al, 2009). These domains are also preferred for evolutionary aspects, because they diverge much more slowly than regions localised outside of membranes (Oberai et al, 2009).…”
Section: +mentioning
confidence: 99%
“…This algorithm is based on large-scale evaluation of proteins with established TMDs (Bernsel et al, 2009). These domains are also preferred for evolutionary aspects, because they diverge much more slowly than regions localised outside of membranes (Oberai et al, 2009).…”
Section: +mentioning
confidence: 99%
“…We built a phylogeny using the naive MSA, and we built two phylogenies each from the structural unmasked and masked MSAs. Previous work has shown that combined structural and functional constraints impose differing selection pressures in TM vs. extramembrane (EM) domains, in turn producing distinct amino-acid frequency distributions in each domain class (Tourasse and Li, 2000;Stevens and Arkin, 2001;Julenius and Pedersen, 2006;Oberai et al, 2009;Spielman and Wilke, 2013;Franzosa et al, 2013). As our structurally-curated MSAs allowed us to precisely identify each MSA column as either TM or EM, we were able to conduct far more rigorous phylogentic inference using a partitioned analysis.…”
Section: Structurally-aware Msa Strongly Improves Phylogenetic Inferencementioning
confidence: 99%
“…17 We have found that membrane proteins increase van der Waals packing contributions relative to soluble proteins by increasing the overall level of side-chain burial, rather than by improved packing efficiency (volume occupied by atoms). 18,19 Nevertheless, either increased packing efficiency or increased burial could be an important factor in stabilizing membrane proteins in hot environments. 15 We therefore investigated whether packing density and burial are different in mesophiles and thermophiles.…”
Section: Burial and Packingmentioning
confidence: 99%